Tetrabenzeneaza macrocycle: A novel platform for universal high-performance hole transport materials. (February 2021) - Zhu, Jiangnan; Song, Wenxuan; Zhang, Tianmei; Dong, Qingchen; Huang, Jinhai; Zhou, Haitao; Su, Jianhua
Abstract: In this research, a novel macrocycle containing tetrabenzeneaza has been developed as a novel building block for hole transport materials (HTMs). Benefiting from its unique highly twisted spatial configuration, this macrocycle exhibits high triplet energy level ( E T) as well as high hole mobility. Based on this aza macrocycle, two hole transporting materials, namely 2TPATPCA and 2CzTPCA, were designed and synthesized. Both 2TPATPCA and 2CzTPCA possess enough E Ts, appropriate frontier orbital energy levels as well as good thermal stability, which promote them as universal HTMs in multicolor phosphorescent organic light-emitting devices (PhOLEDs) and thermal activated delay fluorescence (TADF) OLEDs. High external quantum efficiencies (EQEs) were realized in OLEDs using the these two HTMs. For example, sky bule PhOLED with 2CzTPCA showed a significantly improved maximum EQE of 20.3% compared to that of the reference device using N, N′-Bis(naphthalen-1-yl)-N, N′-bis(phenyl)benzidine (NPB ) (EQE of 14.2%) and 4, 4′-Cyclohexylidenebis[N, N- bis(4-methyl phenyl)aniline (TAPC ) (EQE of 12.2%). Green TADF OLED using 2CzTPCA as HTM also exhibit a much improved maximum EQE of 17.9% compared to that of the reference device based on NPB (EQE of 10.3%). These results indicate this tetrabenzeneaza macrocyclic is a promising building block for developing universal high-performance HTMs. Graphical abstract: Image 1 Highlights: Developed a novel platform – tetrabenzenacyclohexaphane for building HTMs. Tetrabenzenacyclohexaphane derivatives exhibited high triplet energies, good thermal stability, and high hole-transporting abilities. Universal HTMs based on tetrabenzenacyclohexaphane in multicolor PhOLEDs and TADF OLEDs exhibited superior performance.